(untitled) (Entrepreneurship Journal for Finance and Business, 2020)
The research discussed the importance of non-financial information and the extent of its disclosure and its reflection on the market value of Iraqi commercial banks. The research sample included in the Iraq Stock Exchange, as a list of information required to be disclosed in banks consisting of (67) elements was prepared, and applied to each of the banks as a sample Research to find out whether the bank discloses the information or not, and the information was divided into four groups: a strategy, a non-financial financial, and another to measure the independent variable represented by the non-financial disclosure, while the average annual price of the share was used as a measure to measure the dependent variable represented by the market value of bank shares, which is It is extracted by (the annual trading volume of the bank the number of shares traded), and among the most important conclusions reached by the research are: There is no correlation and moral impact between the non-financial disclosure and the market value. While the research concluded with presenting a set of recommendations, the most important of which are: The need for investors to be aware of the importance of non-financial disclosure as it provides additional information related to risk management such as risks (credit, market, liquidity, interest rates, foreign currency) and future expectations regarding stock prices, cash flows, revenues and profits. And capital expenditures, given that the disclosure of financial information does not provide investors with the future evaluation of the bank and the ability to fully understand the opportunities and risks, which helps them in the process of visualizing future risks and opportunities in addition to evaluating the financial expectations of the bank in the distant future, which enables them to make a rational decision in investing in the bank’s shares.